Systematic Review of Knowledge Acquisition and Representation Techniques - Forero, Diana Magally; Martínez Acevedo, Álvaro Javier; Pinto Prieto, Laura Patricia; Becerra Ardila, Eduardo (TECCIENCIA, 2014)
The need to create mechanisms or systems to acquire, represent, and convey knowledge is one of the problems that have been given priority over years of research; the need for acquisition has generated the need for more compact models that conserve implicit and explicit knowledge generated within organizations. Within this environment, due to changes generated by knowledge management, enterprises recognize the importance of managing these intangible assets as a requirement to stay in the market and adapt to organizational and technological changes. Each organization must find its own way and recognize that intellectual capacity has become an important factor for the success of organizational development. The aim of this paper was to present the results of a systematic literature review through which we identified some knowledge acquisition and representation techniques that can be replicated in organizations to leverage internal and external knowledge to the organization and achieve sustainable competitive advantages. The results present administrative techniques related to organizational culture and values, as well as the definition of different types of alliances also identified as expert system technologies and social tools useful for knowledge acquisition and representation.